Residential exposure to traffic noise and risk of incident atrial fibrillation: A cohort study. (July 2016) - Monrad, Maria; Sajadieh, Ahmad; Christensen, Jeppe Schultz; Ketzel, Matthias; Raaschou-Nielsen, Ole; Tjønneland, Anne; Overvad, Kim; Loft, Steffen; Sørensen, Mette
Abstract: Background: Studies have found long-term exposure to traffic noise to be associated with higher risk for hypertension, ischemic heart disease and stroke. We aimed to investigate the novel hypothesis that traffic noise increases the risk of atrial fibrillation (A-fib). Methods: In a population-based cohort of 57, 053 people aged 50–64 years at enrolment in 1993–1997, we identified 2692 cases of first-ever hospital admission of A-fib from enrolment to end of follow-up in 2011 using a nationwide registry. The mean follow-up time was 14.7 years. Present and historical residential addresses were identified for all cohort members from 1987 to 2011. For all addresses, exposure to road traffic and railway noise was estimated using the Nordic prediction method and exposure to air pollution was estimated using a validated dispersion model. We used Cox proportional hazard model for the analyses with adjustment for lifestyle, socioeconomic position and air pollution. Results: A 10 dB higher 5-year time-weighted mean exposure to road traffic noise was associated with a 6% higher risk of A-fib (incidence rate ratio (IRR): 1.06; 95% confidence interval (95% CI): 1.00–1.12) in models adjusted for factors related to lifestyle and socioeconomic position. The association followed a monotonic exposure–response relationship. In analyses with adjustment for air pollution, NOx or NO2, there were no statistically significant associations between exposure to road traffic noise and risk of A-fib; IRR: 1.04; (95% CI: 0.96–1.11) and IRR: 1.01; (95% CI: 0.94–1.09), respectively. Exposure to railway noise was not associated with A-fib. Conclusion: Exposure to residential road traffic noise may be associated with higher risk of A-fib, though associations were difficult to separate from exposure to air pollution. Highlights: Traffic noise is associated with higher risk for cardiovascular disease. No studies have investigated association between noise and atrial fibrillation. In our study cohort of 50, 242 participants 2692 developed atrial fibrillation. Residential road traffic noise seemed associated with risk of atrial fibrillation. The association was however difficult to separate from exposure to air pollution.